The Effect of Dysphagia Education Through Video on the Level of Knowledge and Screening of Dysphagia and Self-Efficacy of Nurses - Syahrun; Hani, Alfriana; Rahayu, Masruroh (LPPM Undiksha, 2022)
This study aims to analyze the effect of dysphagia education through knowledge level videos, dysphagia screening, and nurse self-efficacy. The method used descriptive method of analytic entitle True experimental with pretest and posttest control group design. The number of respondents 35 nurses selected using purposive sampling. Data collection used Self-Administered Questionnaire instrument, Questionnaire Modified Nursing Dysphagia Screen, and Generalized Self-Efficacy Scale (GSE-10) and analyzed using T-test dependent samples. The result was significantly the level of dysphagia knowledge in the control group (p value = 0.017), the video group (p value = 0.002). Significant results also occurred at the knowledge level of dysphagia screening in the video group. Meaningless results occurred in the control group at the knowledge level of dysphagia screening and self-efficacy of nurses, as well as self-efficacy in the video group. As shown in educational research dysphagia through video can affect the level of knowledge and level of knowledge of dysphagia screening but is not able to influence the self-efficacy of nurses.